Perspectives of Ukrainian-Polish economic cooperation - Shevchenko, Maryna Mykolaivna; Klepikova, S. V. (НТУ "ХПІ", 2015)
Discusses the results of the studies of external economic relations of Ukraine and Poland in the years 2003-2015. Offers recommendations for the development of bilateral economic relations at the state level, regions and enterprises.

Обговорюються результати досліджень зовнішньо економічних зв'язків України та Польщі в 2003-2015 роках. Пропонуються рекомендації з розвитку двосторонніх економічних відносин на державному рівні, регіонів і підприємств.
Перспективи українсько-польського економічного співробітництва
Keywords: international business; globalization; joint ventures; integration; міжнародний бізнес; глобалізація; створення спільних підприємств